Rare case of iatrogenic aortic valve leaflet tear following a diagnostic coronary angiogram. Issue 1 (1st October 2019) - Madigan, Mariah; McIsaac, Sarah; Garg, Avinash; Alqahtani, Abdul; Kumar, Andreas; Atoui, Rony
Abstract: We report a rare case of a 44‐year‐old male who underwent a diagnostic coronary angiogram following a non‐ST elevation myocardial infarction complicated by an aortic valve leaflet tear requiring surgical intervention. Routine transthoracic echocardiogram demonstrated a mobile echogenic structure prolapsing into the left ventricular outflow tract. An intraoperative transesophageal echocardiogram confirmed that the structure originated from the ventricular side of left coronary cusp, causing malcoaptation between left and right coronary cusps, and subsequent moderate to severe aortic regurgitation.